Forecasting the Economic Demand for Occupational Education - KOSORUKOV, Oleg A. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article deals with the dynamic model of the regional labor market. This model aims at the development of optimal structure of professional training, with regard to the socio-economic development and the labor market dynamics. The study also considers the problem of optimal placement of students in the system of educational institutions dealing with occupational education. The article provides mathematical description of the basic processes, related to the labor market, and describes the requirements for model functions and methods for finding the model parameters. The study also provides the required source data for the proposed model. The method of mathematical modeling was used as a tool required for taking management decisions. The system-dynamic modeling was used as the main method of mathematical modeling. The article introduced and described endogenous and exogenous model parameters. The required equations determining the dynamics of the processes are provided. The author proposed parametric classes of functions with a view to describe relevant processes and described algorithms to evaluate their parameters as well as the related statistical and expert data. In conclusion, the author introduced and described endogenous and exogenous model parameters as well as equations required for determining the dynamics of relevant processes. The author proposed parametric classes of functions with the view of describing relevant processes and provided algorithms to evaluate their parameters as well as related statistical and expert data.
Keywords: labor market, regional economy, staff turnover models, economic demand, labor migration